Innovative Entrepreneurship Education: Positing an Integrative Model - Egharevba, Etinosa Matthew; Ukenna, Stephen Ikechukwu; Ogbari, Mercy Ejovwokwoghene; Barnabas, Suleiman M.; Oke, Ugbenu; Gayus, Kasa Adamu (Advances in Social Sciences Research Journal, 2022)
This conceptual paper is triggered by the backdrop that graduates emerging from the developing countries, particularly in the sub-Saharan African region seem not to be strong enough in their personal capacity, resolve and drive to becoming independent entrepreneurs, perhaps as a result of fear, inertia, and unwillingness to take-risk. These drawbacks somewhat suggest that prevailing innovative entrepreneurship educative models may be pedagogically inadequate. The study reviews existing models underpinning innovative entrepreneurship. Secondary sources of data was employed to provide broad insights on the domain of innovative entrepreneurship and related areas. This paper advocates for a departure from the current theoretical approach to the adoption of the Integrative Model of Innovative Entrepreneurship Education (IMIEE), which is a pragmatic mechanism for the study of entrepreneurship education and curriculum development in developing countries. The integrative model of innovative entrepreneurship education is imperative for understanding and guidance in pedagogy and practice such that drives innovative entrepreneurship practice and institutional sustainability.